Integrated Crop–Livestock Systems as a Strategy for the Sustainable Production of Corn and Soybean Grain in Tropical Sandy Soils - Soares, Deyvison de Asevedo (2024)
Integrated crop–livestock systems (ICLS) have sustainably intensified modern agricultural practices worldwide. This research assessed how production systems and crop types impact the chemical properties of an Oxisol in the Brazilian Cerrado, the grain yield of corn intercropped with palisade grass (Urochloa) in the off-season in an ICLS, and the grain yield (GY) of soybean in succession. Intercropped and monocropped systems were assessed in a three-year field experiment: corn + Urochloa ruziziensis–soybean; corn + U. brizantha cv. Piatã–soybean; corn + U. brizantha cv. Paiaguás–soybean (ICL–Paiaguás); corn–soybean under a no-tillage system (NTS); corn–soybean under a conventional tillage system (CTS); Piatã grass–continuous grazing (Perennial Piatã); and Paiaguás grass–continuous grazing (Perennial Paiaguás). The residual impact of phosphate fertilization was more pronounced in the ICLS treatments. In the soil layer from 0.0 to 0.2 m depth, ICLS–Paiaguás and Perennial Piatã had the most positive effects on soil chemical quality. In the last year, grain yield was highest in corn monoculture under the NTS and soybean in succession under the ICLS. ICL–Paiaguás improved soil chemical properties for soybean in succession. These results confirm that an intermittent pasture system for legume crops in sequence is an alternative that can maintain or improve soil chemical composition, and that CTS should be avoided in tropical sandy soils.